The impact of VC ownership concentration on the performance of portfolio firms: Evidence from the UK - Wu, Changjian (2019)
The paper mainly investigates whether the relationship between ownership concentration of venture capitalists and firm performance is quadratic (inverted U-shaped). The unbalanced panel data includes 127 VC-funded and 254 non-VC-funded firms from different industries in the UK. The period of the dataset is ten years (2009-2018). After controlling endogeneity by using two-stage system GMM, the results are significant and robust: the lower level of VC ownership concentration is positively correlated with firm performance, while the higher level of concentrated ownership of VC is negatively associated with firm performance. Namely, their relationship is an inverted U-type. Moreover, the turning points are also calculated. Firms have the highest ROE when VC concentrated ownership reaches 53.6; when VC ownership concentration reaches 37.5, the company will have the highest ROA. In addition, the following results are also examined by this paper: 1) firms without VC participation have lower profitability than VC invested companies; 2) VC syndicated deals outperform investments without VC syndication; 3) if an investment involves international venture capitalists, it has lower performance compared to investment without international VC investors.